Efficacy of wearable transcutaneous electrical acupoint stimulation bracelet on moderate-to-severe postoperative nausea and vomiting in patients after general anesthesia: a study protocol for a multicenter randomized controlled trial - Peng Ding; Dong-yu Zheng; Hong-wei Zhu; Ming Gong; Yong-qiang Wang; Ling-yan Jin; Guang-li Ren; Hui-jing Shi; Yong-hua Li (Trials)
Abstract Background Postoperative nausea and vomiting (PONV) is the most common complication following general anesthesia. Currently, pharmaceutical therapy is the primary method of treatment, but it has reached a plateau, and it is accompanied by inherent adverse reactions and high costs. Stimulation of the wrist acupuncture point PC6 is recommended as an effective means of preventing PONV. Our previous study suggests that the wearable transcutaneous electrical acupoint stimulation (TEAS) bracelet can prevent PONV, but its effectiveness in treating moderate-to-severe PONV that has already occurred remains unknown. This trial aims to include female patients who have suffered from PONV after general anesthesia in real-world settings to investigate the therapeutic effect of the TEAS bracelet. Methods This trial will be conducted in Shanghai and Tianjin, China, with a total of 232 participants recruited from four academic hospitals. Participants will be randomly allocated into the TEAS group or the control group in a 1:1 ratio. Participants in the TEAS group will wear an EmeTerm bracelet and be injected with normal saline, while participants in the control group will wear a model bracelet and be injected with 10 mg of metoclopramide. Follow-up will be conducted 2 h later, and participants who do not experience relief will be randomly allocated into two groups and given cross-intervention. The primary outcome of the trial is the response rate of moderate-to-severe PONV after 2 h of intervention. Secondary outcomes include the recurrence rate of moderate-to-severe PONV within 24 h after intervention and the response rate of moderate-to-severe PONV at 2 h after cross-intervention in a population insensitive to the initial intervention. Discussion This multi-center randomized controlled trial aims to reveal the therapeutic effect of the wearable TEAS bracelet on PONV. It is expected that this bracelet will become an effective supplement for the clinical treatment of PONV, reducing medical expenditure and improving anesthesia quality and patient satisfaction. Trial registration Chinese Clinical Trial Registry ChiCTR2400084329. Registered on May 14, 2024.